The Space Between Us: A Social-Functional Emotions View of Ambivalent and Indifferent Workplace Relationships - Methot, Jessica R.; Melwani, Shimul; Rothman, Naomi B. (Journal of Management, 2017)
Workplace relationships are a cornerstone of management research. At the same time, there remain pressing calls for work relationships to be front and center in management literature, demanding an organizationally specific “relationship science.” This article addresses these calls by unifying multiple scholarly fields of interest to develop a comprehensive understanding of interpersonal workplace relationships. Specifically, in this review, we move beyond the tendency to pit positive and negative relationships against each other and, instead, spotlight theory and research associated with ambivalent and indifferent relationships, which are prevalent and impactful yet persistently understudied. We organize our review into four streams: sources, outcomes, dynamics, and measurement. We then advance existing workplace relationships literature by integrating the social functions of emotions perspective. In doing so, we move beyond the positive–negative dichotomy by implicating discrete emotions and their interpersonal functions for workplace relationships. We conclude by offering an agenda for future scholarship.